ASUHAN KEBIDANAN TERHADAP IBU HAMIL DENGAN KEJADIAN PREEKLAMPSIA - Ulpawati; susanti; Miftahul Jannah (Universitas Batam, 2022)
Preeclampsia is a syndrome characterized by increased blood pressure, proteinuria, and fluid retention that appears in the second trimester of pregnancy or more than 20 weeks and will recover in the postnatal period. The purpose of this study was to carry out midwifery care for pregnant women with mild preeclampsia. The research method is a case study with Varney's 7-step Antenatal Midwifery Care Management and documentation in SOAP at BPM Suratmi, Batam City. The case study results were conducted on Mrs